Decreased hemodynamic response in inferior frontotemporal regions in elderly with mild cognitive impairment. (30th April 2018) - Katzorke, Andrea; Zeller, Julia B.M.; Müller, Laura D.; Lauer, Martin; Polak, Thomas; Deckert, Jürgen; Herrmann, Martin J.
Abstract: The verbal fluency task (VFT) is a well-established cognitive marker for mild cognitive impairment (MCI) in the prodromal stage of Alzheimer´s dementia (AD). The behavioral VFT performance of patients allows the prediction of dementia two years later. But effective compensatory mechanism might cover or reduce the predictive value of the VFT. Therefore the aim of this study is to measure the hemodynamic response during VFT in patients with mild cognitive impairment (MCI) to establish the hemodynamic response during the VFT as a screening instrument for the prediction of dementia. One method which allows measuring the hemodynamic response during speech production without severe problems with moving artifacts like in functional magnetic resonance imaging (fMRI) is the functional near-infrared spectroscopy (fNIRS). It is optimal as a screening instrument, as it is easy to apply and without any contraindications. In this study we assessed the hemodynamic response in prefrontal and temporal regions in patients with MCI as well as matched healthy controls with fNIRS. We found a decreased hemodynamic response in the inferior frontotemporal cortex for the MCI group. Our results indicate that a frontotemporal decreased hemodynamic response could serve as a diagnostic biomarker for dementia. Highlights: Elderly with MCI exhibit a hypoactivation of the inferior frontotemporal cortex. We found no hemisphere lateralization in the elderly (healthy and MCI). Correlation of performance and brain activity differs for MCI and healthy elderly.